Boko Haram: African Islamic State - Gvilia, Tsotne (My University, 2021)
Boko Haram, also known as the African Islamic State, has become one of the major problems for the Chadian Lake Basin states. A terrorist organization is busy with destabilizing countries because they give neither peaceful settlements nor states a break. Boko Haram continues to commit terrorist acts that are claiming the lives of more people, and that is why this topic was chosen to understand what this terrorist organization represents. Those reasons determined the topic of this dissertation. Boko Haram clashes include suicide bombers, as well as the use of conventional weapons against both civilians and the military. Boko Haram jihadists rely on stealth, using both locals and rural areas for this. The Boko Haram skirmishes became topical in the early 2000s, but emerged in 2009, when their active involvement began. In 2009, the Nigerian military arrested members of Boko Haram and confiscated ammunition and bomb-making materials. This resulted in Boko Haram attacking police in the following cities: Maiduguri, Potiskum, Bauchi in Yobe State, Wudil and Kano. More than 700 people were killed and police buildings, prisons and state buildings, schools, churches were destroyed. Recall the Bauchi prison break that occurred on September 7, 2010. After the election of a new leader, Boko Haram released from prison 105 members and in addition 600 other prisoners escaped. This was followed by new clashes in Nigeria, especially in the north of the country. A few months later, Boko Haram detonated 4 bombs in Jos and struck two churches in Maiduguri, while on New Year's Eve, Boko Haram blew up barracks, killing civilians. The following year 2011 did not turn out to be easy for Nigeria either. Hours before President Goodluck Jonathan's inauguration, Boko Haram carried out a series of bombings in Abuja, Zaria and Bauchi. In 2012, there were small-scale clashes between Christians and Igbo ethnic groups in the country. In Kano, a police building was hit, killing 190 people. Clashes were strong from 2013 to 2021 as well. In 2021, Boko Haram killed 10 people in Maiduguri, and in April ISWAP killed 33 military personnel in Borno state. Boko Haram continues to carry out attacks on the Nigerian state and military forces today, but let us recall the old terrorist acts in Europe. In September 1972, the city of Munich hosted the Olympic Games. Munich had mainly symbolic value since Germany was then divided into two parts, providing an opportunity to celebrate Olympic ideals of peace and togetherness. Sadly, terrorist attack tested these ideas. iii The attack was initiated by a group that referred to itself as "Black September", and its founder was Ali Hassan Salameh, originally from Palestine, codenamed Abu Hassan. The attackers disguised as police officers who were armed and ordered to kill members of the Israeli delegation. They also blew up a plane and killed Olympic participants. Thirty years later, another tragedy occurred in the Western world. The terrorist attacks of September 11, 2001, which primarily targeted twin commercial buildings in upstate New York, demonstrated the dangers of terrorists' attacks on a grand scale. This event played a turning point in the changing world. In particular, pressure on the Middle East and the places where Osama Bin Laden lived has increased, international organizations-imposed sanctions, and U.S. troops entered Afghanistan and Iraq under the command of George W. Bush1 to bring peace to Iraq. The event is known as the Bush Doctrine, meaning the U.S. declared war on international terrorism after the 9/11 terrorist attacks. Unfortunately, terrorism could not get reduced, and about 200 thousand terrorist acts were carried out from 2001 to 2020. In addition, it should be noted that the coronavirus pandemic has had a significant impact on the Islamic State, as they have taken a "pause" to carry out terrorist acts. That is why attention needs to be paid to the fight against terrorism, because any of us may be one of the victims tomorrow if people do not pay proper attention to all this. However, unfortunately, the African continent is under pressure from terrorists, and their area and power are expanding, so this dissertation serves the purpose of presenting the biggest problem in some of African states, the terrorist group Boko Haram, now known as Boko Haram, the African Islamic State
A research report submitted in partial fulfilment of the requirements for the degree Master of Arts in Political Studies to the Faculty of Humanities, School of Arts, University of the Witwatersrand, 2021